A writing center practitioner's inquiry into collaboration : pedagogy, practice, & research - Nordstrom, Georganne (New York, NY : Routledge, 2021)
"This book presents a model of Practitioner Inquiry (PI) as a systematic form of empirical research and provides a rationale for its suitability within a writing center context. Exploring the potential of writing centers as pedagogical sites that support research, the book offers an accessible model that guides both research and practice for writing center practitioners, while offering flexibility to account for their distinct contexts of practice. Responding to the increasing call in the field to produce empirical "RAD" (replicable, aggregable, data-driven) research, the author explores Practitioner Inquiry through explication of methodology and methods, a revisitation of collaboration to guide both practice and research, and examples of application of the model. Nordstrom grounds this research and scholarship in Hawaiʻi's context and explores Indigenous concepts and approaches to inform an ethical collaborative practice. Offering significant contributions to empirical research in the fields of writing center studies, composition and education, this book will be of great relevance to writing center practitioners, anyone conducting empirical research, and researchers working in tutor professionalization, collaboration, translingual literacy practices, and research methodologies"--
OCLC-licensed vendor bibliographic record.
Keywords: Writing centers -- Research -- Methodology; English language -- Rhetoric -- Study and teaching -- Research -- Methodology; Interdisciplinary approach in education -- Case studies; English language -- Composition and exercises -- Study and teaching; Writing centers -- Hawaii; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing